Pre-treatment Ongoing Cortical Oscillatory Activity Predicts Improvement of Tinnitus After Partial Peripheral Reafferentation With Hearing Aids - Han, Jae Joon; Ridder, Dirk De; Vanneste, Sven; Chen, Yu-Chen; Koo, Ja-Won; Song, Jae-Jin (Frontiers in Neuroscience, 2020)
Although hearing aids (HAs) are sometimes efficacious in abating tinnitus, the precise mechanism underlying their effect is unclear and predictors of symptom improvement have not been determined. Here, we examined the correlation between the amount of tinnitus improvement and pre-HA quantitative electroencephalography (qEEG) findings to investigate cortical predictors of improvement after wearing HAs. QEEG data of Thirty-three patients with debilitating tinnitus were retrospectively correlated with the percentage improvements in tinnitus handicap inventory and numerical rating scale scores of tinnitus. Activation of brain areas involved in the default mode network (DMN; inferior parietal lobule, parahippocampus, and posterior cingulate cortex) were found to be a negative predictor of improvement in tinnitus-related distress after wearing HAs. In addition, higher pre-HA cortical power at the medial auditory processing system or higher functional connectivity of the lateral/medial auditory pathway to the DMN was found to serve as a positive prognostic indicator with regard to the improvement of tinnitus-related distress. In addition, insufficient activity of the pre-treatment noise canceling system tended to be a negative predictor of tinnitus perception improvement after wearing HAs. The current study may serve as a milestone toward a pre-HAs prediction strategy for tinnitus improvements in subjects with hearing loss and severe tinnitus.